ANSWER
![(4n - 1)\sqrt{3 n} + 3\sqrt{n}](https://tex.z-dn.net/?f=%284n%20-%201%29%5Csqrt%7B3%20n%7D%20%2B%203%5Csqrt%7Bn%7D)
EXPLANATION
The given expression is
![\sqrt{48 {n}^{3} } + \sqrt{9n} - \sqrt{3n}](https://tex.z-dn.net/?f=%20%5Csqrt%7B48%20%7Bn%7D%5E%7B3%7D%20%7D%20%20%2B%20%20%5Csqrt%7B9n%7D%20%20-%20%20%5Csqrt%7B3n%7D%20)
We remove the perfect squares under the radical sign.
![\sqrt{16 {n}^{2} \times3 n} + \sqrt{9n} - \sqrt{3n}](https://tex.z-dn.net/?f=%5Csqrt%7B16%20%7Bn%7D%5E%7B2%7D%20%20%5Ctimes3%20n%7D%20%20%2B%20%20%5Csqrt%7B9n%7D%20%20-%20%20%5Csqrt%7B3n%7D%20)
We can now take square root of the perfect squares and simplify them further.
![\sqrt{16 {n}^{2}} \times \sqrt{3 n} + \sqrt{9} \times \sqrt{n} - \sqrt{3n}](https://tex.z-dn.net/?f=%20%5Csqrt%7B16%20%7Bn%7D%5E%7B2%7D%7D%20%20%20%5Ctimes%20%5Csqrt%7B3%20n%7D%20%2B%20%20%20%5Csqrt%7B9%7D%20%5Ctimes%20%20%5Csqrt%7Bn%7D%20%20-%20%20%5Csqrt%7B3n%7D%20)
This simplifies to:
![4n\sqrt{3 n} + 3\sqrt{n} - \sqrt{3n}](https://tex.z-dn.net/?f=4n%5Csqrt%7B3%20n%7D%20%2B%203%5Csqrt%7Bn%7D%20%20-%20%20%5Csqrt%7B3n%7D%20)
This further simplifies to:
![(4n - 1)\sqrt{3 n} + 3\sqrt{n}](https://tex.z-dn.net/?f=%284n%20-%201%29%5Csqrt%7B3%20n%7D%20%2B%203%5Csqrt%7Bn%7D%20)
you cannot multiply any of the numbers above by another to get 12, the factors of 12 would be 1,2,3,4,6,12 1x12= 12 2x6=12 4x3=12
The answer is (14) just add them all up
Answer:
35.2
Step-by-step explanation:
tan(58) = x/22
or, x = 22×tan(58)
or, x = 35.2 (rounded to the nearest tenth)
Answered by GAUTHMATH